Novel monoclonal antibody to fibrin(ogen) αC-region for detection of the earliest forms of soluble fibrin - N. E. Lugovska; I. M. Kolesnikova; Ye. M. Stohnii; V. O. Chernyshenko; A. V. Rebriev; O. P. Kostiuchenko; G .K. Gogolinska; N. A. Dziubliuk; L. D. Varbanets; T. M. Platonova; S. V. Komisarenko (The Ukrainian Biochemical Journal, 2020)
Obtaining new monoclonal antibodies (mAbs) towards fibrin(ogen) and its fragments is an important task for studying mechanisms of blood clot formation, searching for novel antithrombotic agents and developing immunodiagnostics. The aim of the present work was to create and characterize a new mAb towards the fibrin(ogen) αС-region. We surmise that having a specific mAb towards this flexible part of the molecule will allow us to study the role of the αС-region in fibrin polymerization and also to develop an approach for detecting the earliest forms of soluble fibrin by sandwich ELISA. Using hybridoma technology we оbtained mAb 1-5A to the αC-region of fibrinogen.. It was characterized using several variations of ELISA and Western blot. Application of specific proteases together with MALDI-TOF analysis allowed us to localize its epitope that is located in fragment 537-595 of the Aα-chain of fibrin(ogen). МAb 1-5A can be used as a detecting tag-antibody in sandwich ELISA for the quantification of the earliest forms of soluble fibrin which are uncleaved by plasmin and preserved C-terminal portions of αC-regions. These earliest forms of soluble fibrin are direct evidence of blood coagulation system activation, thrombin generation and the danger of intravascular thrombus formation. Their determination will provide additional, more accurate information about the state of the blood coagulation system and the risk of blood clotting, which is very important for the timely and correct selection of adequate antithrombotic therapy. MAb 1-5A effectively binds the αC-containing molecules of fibrinogen and fibrin in blood plasma. It also can be used for studying protein-protein and protein-cellular interactions of the αC-regions of fibrin(ogen).